A colloidal battery electrolyte, preparation method and colloidal battery

By developing a colloidal battery electrolyte prepared from multiple components, the problems of stratification and sulfation of ordinary lead-acid battery electrolytes are solved, the cycle life and high-temperature floating charging life of the battery are improved, and the stability and gel performance of the colloid are improved.

CN119786759APending Publication Date: 2025-04-08ANHUI LEOCH POWER SUPPLY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411781059.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In use, ordinary lead-acid batteries have problems such as electrolyte layering and sulfate suction. The gel condition of the colloidal battery electrolyte is not ideal, is difficult to infuse, the colloid is unstable, and the water loss is serious, which affects the battery's cycle life and high-temperature floating charging life.

Method used

A colloidal battery electrolyte prepared from components such as vapor phase silica, dilute sulfuric acid, p-aminobenzamide, phosphoric acid, glycerol, anhydrous sodium sulfate, stannous sulfate, benzoate, zinc sulfate, polytetrafluoroethylene, polyvinyl alcohol and CMC were developed. The gel performance and stability of the electrolyte were improved through specific preparation methods and component ratios.

Benefits of technology

The electrolyte is evenly distributed inside the battery, improving the irreversible sulfateization of the negative electrode plate, inhibiting the hydrogen evolution loss of the battery, extending the battery's cycle life and high-temperature floating charging life, and improving the stability of the colloid and gel performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786759A_ABST
    Figure CN119786759A_ABST
Patent Text Reader

Abstract

The present application discloses a colloidal battery electrolyte, a preparation method and a colloidal battery, and relates to the technical field of colloidal battery electrolyte. The electrolyte is prepared from the following components: 3.5-5.5wt% of fumed silicon dioxide; 30-40wt% of dilute sulfuric acid; 0.3-0.8wt% of p-aminobenzamide; 0.5-1.0wt% of phosphoric acid; 0.05-0.10wt% of glycerol; 0.8-1.0wt% of anhydrous sodium sulfate; 0.1wt% of stannous sulfate; 0.3-0.5wt% of benzyl benzoate; 0.03-0.13wt% of zinc sulfate; 0.03-0.05wt% of polytetrafluoroethylene; 0.02-0.08wt% of polyvinyl alcohol; 0.2wt% of CMC; the balance of deionized water. Dissolve polyvinyl alcohol and p-aminobenzamide, cool to room temperature to obtain a mixed solution; mix components such as dilute sulfuric acid evenly, add the mixed solution, and introduce it into a stirring kettle; add fumed silica to obtain an electrolyte. A colloidal battery using the above electrolyte. The colloidal electrolyte of the present invention is evenly distributed inside the battery, improves the irreversible sulfation of the negative plate, inhibits the battery from hydrogen evolution and water loss, and prolongs the battery cycle life and high-temperature floating charge life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of colloidal battery electrolyte, and in particular to a colloidal battery electrolyte, a preparation method and a colloidal battery. Background Art

[0002] Lead-acid batteries are widely used due to their abundant raw materials, low prices, mature technology, safety and reliability, and high lead resource recovery rate in waste battery treatment. However, ordinary lead-acid batteries have problems such as electrolyte stratification and easy sulfation during use and cannot meet consumer requirements.

[0003] The silica gel molecules in the electrolyte of the colloidal battery form a porous network structure, which wraps the sulfuric acid electrolyte. During charging, a gel reaction occurs to form cracks, which provide channels for oxygen transmission and facilitate the electrochemical reaction. The colloidal electrolyte is evenly distributed in the middle of the plate, avoiding sulfuric acid stratification. However, ordinary colloidal battery electrolytes also have problems such as unsatisfactory gelation, difficulty in injection, unstable colloid, and severe water loss, which affect the battery's cycle life and high-temperature floating charge life. Summary of the invention

[0004] In order to solve at least one of the above technical problems, a colloidal battery electrolyte with good gel performance is developed. The present application provides a colloidal battery electrolyte, a preparation method and a colloidal battery.

[0005] On the one hand, the present application provides a colloidal battery electrolyte prepared from the following components:

[0006] Fumed silica 3.5-5.5wt%;

[0007] Dilute sulfuric acid 30-40wt%;

[0008] p-Aminobenzamide 0.3-0.8wt%;

[0009] Phosphoric acid 0.5-1.0wt%;

[0010] Glycerol 0.05-0.10wt%;

[0011] Anhydrous sodium sulfate 0.8-1.0wt%;

[0012] Stannous sulfate 0.1wt%;

[0013] Benzoic acid benzyl ester 0.3-0.5wt%;

[0014] Zinc sulfate 0.03-0.13wt%;

[0015] Polytetrafluoroethylene 0.03-0.05wt%;

[0016] Polyvinyl alcohol 0.02-0.08 wt%;

[0017] CMC 0.2wt%;

[0018] Deionized water balance.

[0019] Optionally, the specific surface area of ​​the fumed silica is 200 to 250 m 2 / g.

[0020] Optionally, the temperature of the dilute sulfuric acid is 25°C and the density is 1.28-1.35 g / cm 3 .

[0021] In a second aspect, the present application provides a method for preparing the above-mentioned electrolyte, comprising the following steps:

[0022] S1, heating and dissolving the formulated amount of polyvinyl alcohol and p-aminobenzamide in deionized water, and cooling to room temperature to obtain a mixed solution;

[0023] S2, mixing the formulated amount of dilute sulfuric acid, phosphoric acid, glycerol, sodium sulfate, zinc sulfate, stannous sulfate, benzyl benzoate, polytetrafluoroethylene dispersion, polyvinyl alcohol, CMC and deionized water uniformly, adding the mixed solution prepared in S1, and introducing into a stirring tank;

[0024] S3. Add fumed silica into a stirring kettle and shear it while stirring to obtain an electrolyte.

[0025] Optionally, in S3, the rotation speed of the stirring kettle is 3000 to 5000 rpm, and the stirring time is 20 to 30 minutes.

[0026] Optionally, in S3, the fumed silica is added in multiple times.

[0027] Optionally, in S3, the fumed silica is added in three times, with 50 wt % added in the first time, 30 wt % added in the second time, and 20 wt % added in the third time.

[0028] In a third aspect, the present application provides a colloidal battery using the above-mentioned electrolyte.

[0029] In summary, the present invention includes at least one of the following beneficial technical effects:

[0030] 1. The colloidal electrolyte is evenly distributed inside the battery, improving the irreversible sulfation of the negative plate, inhibiting the battery from hydrogen evolution and water loss, and extending the battery cycle life and high-temperature floating charge life;

[0031] 2. p-Aminobenzamide can be used as a colloid stabilizer to enhance the thixotropic properties of the colloid, and its larger side chain can enhance the uniformity of the colloid distribution;

[0032] 3. Benzoic acid benzyl ester has an inhibitory effect on the crystallization of lead sulfate and can effectively inhibit the sulfation of the electrode plate;

[0033] 4. Zinc sulfate can inhibit battery hydrogen evolution, reduce battery water loss, and extend battery life;

[0034] 5. Polytetrafluoroethylene dispersion can adjust the viscosity of the colloidal electrolyte to meet the required viscosity requirements, and polytetrafluoroethylene can increase the overpotential of hydrogen evolution and also has a certain effect on inhibiting hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a 100% DOD cycle life comparison test diagram of the battery 2 corresponding to the electrolyte of Example 2 and the battery 8 corresponding to the electrolyte of the comparative example;

[0036] Figure 2 This is a high temperature floating charge comparison test diagram of battery 2 corresponding to the electrolyte of Example 2 and battery 8 corresponding to the electrolyte of the comparative example. DETAILED DESCRIPTION

[0037] The present application is further described in detail below with reference to the embodiments.

[0038] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products. Specific embodiments

[0040] Example 1

[0041] Heat and dissolve 0.02 kg of polyvinyl alcohol and 0.3 kg of p-aminobenzamide in deionized water, and cool to room temperature to obtain a mixed solution;

[0042] 30 kg of dilute sulfuric acid, 0.5 kg of phosphoric acid, 0.05 kg of glycerol, 0.8 kg of sodium sulfate, 0.03 kg of zinc sulfate, 0.1 kg of stannous sulfate, 0.3 kg of benzyl benzoate, 0.03 kg of polytetrafluoroethylene dispersion, 0.2 kg of CMC and 64.45 kg of deionized water were mixed evenly, added to the mixed solution prepared in S1, and introduced into a stirred tank;

[0043] 3.5 kg of fumed silica was added into a stirring kettle, and shearing was performed while stirring at a rotation speed of 3000 rpm for 20 minutes to obtain an electrolyte.

[0044] Example 2

[0045] Heat and dissolve 0.05 kg of polyvinyl alcohol and 0.5 kg of p-aminobenzamide in deionized water, and cool to room temperature to obtain a mixed solution;

[0046] 32 kg of dilute sulfuric acid, 0.8 kg of phosphoric acid, 0.08 kg of glycerol, 0.9 kg of sodium sulfate, 0.05 kg of zinc sulfate, 0.1 kg of stannous sulfate, 0.4 kg of benzyl benzoate, 0.04 kg of polytetrafluoroethylene dispersion, 0.2 kg of CMC and 61.38 kg of deionized water were mixed evenly, added to the mixed solution prepared in S1, and introduced into a stirred tank;

[0047] 4 kg of fumed silica was added into a stirring kettle, and shearing was performed while stirring at a rotation speed of 4000 rpm for 20 minutes to obtain an electrolyte.

[0048] Example 3

[0049] Heat and dissolve 0.08 kg of polyvinyl alcohol and 0.8 kg of p-aminobenzamide in deionized water, and cool to room temperature to obtain a mixed solution;

[0050] 35 kg of dilute sulfuric acid, 1 kg of phosphoric acid, 0.1 kg of glycerol, 1 kg of sodium sulfate, 0.08 kg of zinc sulfate, 0.1 kg of stannous sulfate, 0.5 kg of benzyl benzoate, 0.05 kg of polytetrafluoroethylene dispersion, 0.2 kg of CMC and 57.39 kg of deionized water were mixed evenly, added to the mixed solution prepared in S1, and introduced into a stirred tank;

[0051] 4.5 kg of fumed silica was added into a stirring kettle, and shearing was performed while stirring at a rotation speed of 4500 rpm for 25 minutes to obtain an electrolyte.

[0052] Example 4

[0053] Heat 0.05 kg of polyvinyl alcohol and 0.3 kg of p-aminobenzamide in deionized water to dissolve, and cool to room temperature to obtain a mixed solution;

[0054] 38 kg of dilute sulfuric acid, 0.8 kg of phosphoric acid, 0.08 kg of glycerol, 0.9 kg of sodium sulfate, 0.1 kg of zinc sulfate, 0.1 kg of stannous sulfate, 0.3 kg of benzyl benzoate, 0.04 kg of polytetrafluoroethylene dispersion, 0.2 kg of CMC and 54.43 kg of deionized water were mixed evenly, added to the mixed solution prepared in S1, and introduced into a stirred tank;

[0055] 5 kg of fumed silica was added into a stirring kettle, and shearing was performed while stirring at a rotation speed of 3000 rpm for 20 minutes to obtain an electrolyte.

[0056] Example 5

[0057] Heat and dissolve 0.08 kg of polyvinyl alcohol and 0.8 kg of p-aminobenzamide in deionized water, and cool to room temperature to obtain a mixed solution;

[0058] 40 kg of dilute sulfuric acid, 1 kg of phosphoric acid, 0.1 kg of glycerol, 1 kg of sodium sulfate, 0.13 kg of zinc sulfate, 0.1 kg of stannous sulfate, 0.5 kg of benzyl benzoate, 0.05 kg of polytetrafluoroethylene dispersion, 0.2 kg of CMC and 51.34 kg of deionized water were mixed evenly, added to the mixed solution prepared in S1, and introduced into a stirred tank;

[0059] 5.5 kg of fumed silica was added into a stirring kettle, and shearing was performed while stirring at a rotation speed of 4500 rpm for 30 minutes to obtain an electrolyte.

[0060] Example 6

[0061] This embodiment is based on the embodiment 1, and only the adding method of the fumed silica is changed, as follows.

[0062] Heat and dissolve 0.02 kg of polyvinyl alcohol and 0.3 kg of p-aminobenzamide in deionized water, and cool to room temperature to obtain a mixed solution;

[0063] 30 kg of dilute sulfuric acid, 0.5 kg of phosphoric acid, 0.05 kg of glycerol, 0.8 kg of sodium sulfate, 0.03 kg of zinc sulfate, 0.1 kg of stannous sulfate, 0.3 kg of benzyl benzoate, 0.03 kg of polytetrafluoroethylene dispersion, 0.2 kg of CMC and 64.45 kg of deionized water were mixed evenly, added to the mixed solution prepared in S1, and introduced into a stirred tank;

[0064] 3.5 kg of fumed silica was added into the stirring kettle in two portions: 2 kg was added for the first time, and shearing was performed while stirring at a rotation speed of 3000 rpm for 10 minutes; 1.5 kg was added for the second time, and shearing was performed while stirring at a rotation speed of 3000 rpm for 10 minutes; an electrolyte was obtained.

[0065] Example 7

[0066] This embodiment is based on the embodiment 5, and only the adding method of the fumed silica is changed, as follows.

[0067] Dissolve 0.08 kg of polyvinyl alcohol and 0.8 kg of p-aminobenzamide in deionized water by heating, and cool to room temperature to obtain a mixed solution;

[0068] 40 kg of dilute sulfuric acid, 1 kg of phosphoric acid, 0.1 kg of glycerol, 1 kg of sodium sulfate, 0.13 kg of zinc sulfate, 0.1 kg of stannous sulfate, 0.5 kg of benzyl benzoate, 0.05 kg of polytetrafluoroethylene dispersion, 0.2 kg of CMC and 51.34 kg of deionized water were mixed evenly, added to the mixed solution prepared in S1, and introduced into a stirred tank;

[0069] 5.5 kg of fumed silica was added into a stirring kettle in three times, 2.75 kg was added for the first time, and shearing was performed while stirring at a speed of 4500 rpm for 10 minutes; 1.65 kg was added for the second time, and shearing was performed while stirring at a speed of 4500 rpm for 10 minutes; 1.1 kg was added for the third time, and shearing was performed while stirring at a speed of 4500 rpm for 10 minutes; an electrolyte was obtained.

[0070] Comparative Example

[0071] 40 kg of dilute sulfuric acid and 54.5 kg of deionized water were mixed evenly and introduced into a stirring kettle; 5.5 kg of fumed silica was added into the stirring kettle and sheared while stirring at a speed of 4500 rpm for 30 minutes; and an electrolyte was obtained.

[0072] The electrolytes prepared in Examples 1 to 5 and the comparative example were tested at a temperature of 25° C. The test results are shown in Table 1.

[0073] Table 1

[0074] Electrolyte Gel time / min <![CDATA[Conductivity / S*m -1 > Example 1 55 76 Example 2 54 75 Example 3 55 77 Example 4 56 75 Example 5 58 74 Example 6 63 82 Example 7 70 86 Comparative Example 24 55

[0075] It can be seen from Examples 1 to 7, the comparative example and Table 1 that the gel time of the electrolyte prepared by the technical solution of the present application is much higher than that of the comparative example, and the conductivity is also significantly higher than that of the comparative example, which indicates that the electrolyte prepared by the present application has good gel performance and better conductivity.

[0076] By comparing Example 1 with Example 6, and Example 5 with Example 7, it can be seen that in the technical solution of the present application, adding fumed silica in multiple times can increase the gel time of the electrolyte by at least 10% and the conductivity by at least 5%. And when in the technical solution of the present application, the fumed silica is added three times, and 50wt% is added in the first time, 30wt% is added in the second time, and 20wt% is added in the third time, the gel time of the prepared electrolyte can be increased by 20% and the conductivity can be increased by 15%.

[0077] The electrolytes in Examples 1 to 7 and the comparative example were added to batteries to obtain batteries 1 to 8. The cycle life of batteries 1 to 8 was tested (deep cycle 100% DOD, when the discharge capacity is less than 80% of the rated capacity, the test is terminated). The test results are shown in Table 2. The 100% DOD cycle life comparison test diagram of battery 2 corresponding to the electrolyte in Example 2 and battery 8 corresponding to the electrolyte in the comparative example is shown in Table 2. Figure 1 shown.

[0078] Table 2

[0079] Battery ID Electrolyte Cycle life / times Battery 1 Example 1 515 Battery 2 Example 2 509 Battery 3 Example 3 514 Battery 4 Example 4 512 Battery 5 Example 5 518 Battery 6 Example 6 545 Battery 7 Example 7 571 Battery 8 Comparative Example 352

[0080] It can be seen from Table 2 that the battery using the electrolyte prepared in the present application can have a cycle life of more than 509 times, which is significantly improved compared to the battery prepared in the comparative example.

[0081] Among them, the cycle life of the battery using the electrolyte prepared in Example 6 of the present application is increased by nearly 5% compared with the battery using the electrolyte prepared in Example 1 of the present application; the cycle life of the battery using the electrolyte prepared in Example 7 of the present application is increased by more than 10% compared with the battery using the electrolyte prepared in Example 5 of the present application.

[0082] Figure 2 This is a high temperature floating charge comparison test diagram of the battery 2 corresponding to the electrolyte of Example 2 and the battery 8 corresponding to the electrolyte of the comparative example. It can be seen that the technical solution of the present application has better performance than the electrolyte of the comparative example.

[0083] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A colloidal battery electrolyte, characterized in that: Prepared from the following components: Fumed silica 3.5-5.5wt%; Dilute sulfuric acid 30-40wt%; p-Aminobenzamide 0.3-0.8wt%; Phosphoric acid 0.5-1.0wt%; Glycerol 0.05-0.10wt%; Anhydrous sodium sulfate 0.8-1.0wt%; Stannous sulfate 0.1wt%; Benzoic acid benzyl ester 0.3-0.5wt%; Zinc sulfate 0.03-0.13wt%; Polytetrafluoroethylene 0.03-0.05wt%; Polyvinyl alcohol 0.02-0.08 wt%; CMC 0.2wt%; Deionized water balance.

2. The electrolyte according to claim 1, characterized in that The specific surface area of ​​the fumed silica is 200 to 250 m 2 / g.

3. The electrolyte according to claim 1, characterized in that The temperature of the dilute sulfuric acid is 25°C and the density is 1.28-1.35 g / cm 3 .

4. A method for preparing the electrolyte according to claim 1, characterized in that: The following steps are involved: S1, heating and dissolving the formulated amount of polyvinyl alcohol and p-aminobenzamide in deionized water, and cooling to room temperature to obtain a mixed solution; S2, mixing the formulated amount of dilute sulfuric acid, phosphoric acid, glycerol, sodium sulfate, zinc sulfate, stannous sulfate, benzyl benzoate, polytetrafluoroethylene dispersion, polyvinyl alcohol, CMC and deionized water uniformly, adding the mixed solution prepared in S1, and introducing into a stirring tank; S3. Add fumed silica into a stirring kettle and shear it while stirring to obtain an electrolyte.

5. The preparation method according to claim 4, characterized in that: In S3, the rotation speed of the stirring kettle is 3000 to 5000 rpm, and the stirring time is 20 to 30 minutes.

6. The preparation method according to claim 4, characterized in that: In the S3, the fumed silica is added in multiple times.

7. The preparation method according to claim 4, characterized in that: In the S3, the fumed silica is added three times, with 50 wt % added for the first time, 30 wt % added for the second time, and 20 wt % added for the third time.

8. A colloidal battery, characterized in that: The electrolyte of claim 1 is used.